The effect of science technology society (STS) learning model on science literation in physical learning reviewed from cognitive style - Gede Yohanes Arygunartha (Warmadewa University Press, 2018)
The purpose of this study is 1) to analyze differences in scientific literacy of students between groups of students who study learning model STM and learning model of Direct Instruction (DI), 2) to analyze the effect of the interaction between the learning model STM with cognitive style on scientific literacy of students, 3) Analyzing the difference differences in scientific literacy of students between groups of students who study learning model STM and learning model of Direct Instruction (DI) which have a cognitive style field dependent (FD), and 4) to analyze the differences differences scientific literacy of students between groups of students who study learning model STM and learning model of Direct Instruction (DI) which have a cognitive style field independent (FI). This study is a quasi-experimental design with posttest only control group design. The study population was all students of class XI MIA Denpasar Hope Christian High School in the academic year 2018/2019. Decision-class research group based random sampling technique. Data were analyzed with descriptive statistics and ANOVA two lanes. The results of the analysis states the following. (1) there are differences in the results of scientific literacy scores physics, among students who study learning model Science Technology Society (STM) with students learning with learning model DI (F = 79,32; p